Poly-γ-Glutamic Acid Complexed With Alum Induces Cross-Protective Immunity of Pandemic H1N1 Vaccine - Nguyen, Quyen Thi; Kwak, Chaewon; Lee, Wang Sik; Kim, Jaemoo; Jeong, Jinyoung; Sung, Moon Hee; Yang, Jihyun; Poo, Haryoung (Frontiers in Immunology, 2019)
The use of a good vaccine adjuvant may induce a higher immunogenicity profile of vaccine antigens. Here, we developed a new adjuvant by combining poly-γ-glutamic acid (γ-PGA) with alum (PGA/Alum) and investigated its ability to enhance the immunogenicity and the cross-reactive efficacy of pandemic H1N1 (pH1N1) influenza vaccine antigen. PGA/Alum enhanced antigen delivery to draining lymph nodes and antigen-specific immunogenicity in mice using OVA as a model antigen. It also greatly increased OVA-specific antibody production, cytotoxic T lymphocyte (CTL) activity, and antibody-dependent cellular cytotoxicity (ADCC). These abilities of PGA/Alum improved the protective efficacy of pH1N1 vaccine antigen by increasing hemagglutination-inhibition titers, enhancing ADCC and CTL activity, and speeding viral clearance following homologous viral challenge. Importantly, the cross-protective efficacy of pH1N1 vaccine against heterologous viruses [A/Puerto Rico/8/34 (H1N1) and A/Hong Kong/1/1968 (H3N2)] was significantly enhanced by PGA/Alum, and cross-reactive ADCC and CTL activities were observed. Together, our results strongly suggest that PGA/Alum may be a promising vaccine adjuvant for preventing influenza and other infectious diseases.